2018
DOI: 10.1007/s40333-018-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Variations of precipitation characteristics during the period 1960–2014 in the Source Region of the Yellow River, China

Abstract: Precipitation, a natural feature of weather systems in the Earth, is vitally important for the environment of any region. Under global climate change condition, the characteristics of precipitation have changed as a consequence of enhanced global hydrological cycle. The source region of the Yellow River (SRYR), locating within the Qinghai-Tibet Plateau, is sensitive to the global climate change due to its complex orography and fragile ecosystem. To understand the precipitation characteristics and its impacts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…The double mass curve method disclosed a straight line at all stations, showing no breakpoints, which confirms the reliability of the precipitation time series. [39,40] also confirmed such results by using the double mass curve method in their studies conducted in the Yellow River basin, China.…”
Section: Aphrodite Precipitation Datasupporting
confidence: 54%
See 2 more Smart Citations
“…The double mass curve method disclosed a straight line at all stations, showing no breakpoints, which confirms the reliability of the precipitation time series. [39,40] also confirmed such results by using the double mass curve method in their studies conducted in the Yellow River basin, China.…”
Section: Aphrodite Precipitation Datasupporting
confidence: 54%
“…For the analysis of different characteristics of precipitation in the SRIR, the daily precipitation rate was divided into different classes, e.g., 0-10 mm day −1 precipitation was described as light precipitation, 10.1-25 mm day −1 precipitation was described as moderate precipitation, while precipitation greater than 25 mm day −1 was described as heavy precipitation. A similar classification of daily precipitation has been used by different researchers for the analysis of precipitation in different regions [12,13,[40][41][42].…”
Section: Aphrodite Precipitation Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A simulation study by Li et al (2012) suggested that a decline in precipitation, especially in the summer season, is a primary driver of decreasing runoff in the upper reach of Yellow River, while temperature rises may play a secondary role. Iqbal et al (2018) mentioned that the short drought significantly increased (periods without rain for ≤ 10 d) in SRYR, which might result in low soil moisture and hinder the runoff process. Lan et al (2010) also attributed the changes in runoff in the headwater region of Yellow River more to the influence of precipitation than temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The vulnerable natural system in the YRB is of interest to researchers worldwide because it reflects the evolution of water resources under climate change and human activity in the future (Wu et al 2016;Wang et al 2019b). Moreover, the precipitation in the YRB has changed in time and space for decades (Lu et al 2014;Zhang et al 2014Zhang et al , 2019Iqbal et al 2018;Zhao et al 2019), arousing many concerns and prompting research on future precipitation change as well as its impact on hydrology and water resources. The GCMs provide scenario determination and forcing data, forming the basis of climate change projection.…”
Section: Introductionmentioning
confidence: 99%